Legal Protection of Stateless Person in Indonesia: Human Rights Dimensions - Muhammad Ibnu Abil; Daffa Dzaky Adi Shaka; Muhammad Aryaguna Penan; Mehmet Enes Deligöz (Fakultas Hukum Universitas Hang Tuah, 2022)
Stateless people become refugees to go to other countries and settle in that country. causing various problems, from domestic violence to the problem of protecting human rights. This paper aims to discuss legal protection for stateless persons in Indonesian law based on human rights dimensions. This study uses normative research methods with statutory and conceptual approaches. The findings of this study are that Indonesia has not ratified the 1954 Convention Relating to the Status of Stateless Persons, so there is no obligation to accept refugees. Because the Citizenship Law emphasizes that basically it does not recognize Stateless. However, Indonesia has ratified various international agreements, so it must protect and accommodate refugees according to these agreements. In addition, stateless people also have the right to acquire Indonesian citizenship but must meet the requirements set out in the Citizenship Law.